Análise do papilomavírus humano (hpv) 16 e variantes genéticas associadas ao câncer do colo do útero em São Luís - Maranhão, Brasil - SILVA, Rodrigo Lopes da (2018)
Introduction: Cervical cancer is the fourth most common cancer in the world, with more than 265,000 deaths and more than 80% of cases occurring in developing countries. In Brazil, it is the third most frequent type of cancer in this population, and the Human Papillomavirus (HPV) is the etiologic factor for cervical cancer, being associated with approximately 90% of the cases. Among the viral types, HPV 16 shows high oncogenicity and is the most prevalent type in cervical tumors. Evidence suggests that variants of the same type of HPV can biologically and etiologically interfere with the development of cervical cancer. Objective: The objective of this study was to estimate the frequency of intra-HPV 16 variants in cervical cancer samples from women diagnosed in two reference hospitals in Oncology in the municipality of São Luís, Maranhão, from 2016 to 2017. Socio-demographic data were obtained through questionnaires applied to the patients. Material and methods: Tumor fragments of the cervix were collected and submitted to DNA extraction and Polymerase Chain Reaction (PCR) reactions were performed to detect HPV. The Nested PCR technique used primers PGMY09 / 11 for the first round and GP+5/6 for the second round. Positive samples were submitted to automated sequencing technique for viral genotyping. For the characterization of HPV 16 strains, positive samples were submitted to PCR using specific primers for amplification of the LCR and E6 regions of HPV 16 virus. Results: Data from 120 patients with cervical cancer were analyzed. Among the patients, (44/36.67%) had primary schooling (51/42.50%), family income between 1 and 2 minimum wages (66/55%) and are married/consensual union (62/51.67%). There was no statistically significant result between HPV association and socio-demographic variables associated with risk factors for cervical cancer (p <0.05). HPV was present in 88 women (73%). The most prevalent types were HPV 16 (47/54%), HPV 18 (12/13.8%), HPV 35 (6/6.9%) and HPV 45 (5/5.7%). Among 47 positive for HPV 16, in 23 samples was identified A variant (49%) followed by D variant in 19 cases (40%) and B and C variants with 2 cases each (4%). The most prevalent histological type in HPV 16 tumors was epidermoid carcinoma in 34 samples (72%), followed by adenocarcinoma in 5 samples (11%). We found a statistically significant association between the HPV 16 variants and the histological types of the tumors studied (p<0,001). Conclusion: Knowledge of HPV 16 variants will provide insights into the influence of pathological and oncogenic cancers of cervical lesions.